Quality of Work Life among Administrative Staff in Public Education Schools in the Riyadh Region (International Journal of Financial, Administrative and Economic Sciences, 2025)
The study aimed to identify the level of quality of work life among the administrative staff in public schools in the Riyadh region, measuring its five dimensions (participation in decision-making, leadership pressure, work-life balance, wages and rewards, and job stability and security). It also identified differences in these dimensions based on gender, educational qualifications, and years of experience.The descriptive-analytical approach was used due to its suitability for the nature of the subject, which aims to describe and explain current administrative phenomena. The study relied on a questionnaire distributed to a sample of (126) male and female administrators in public elementary, middle, and secondary schools in Riyadh.The results of the statistical analysis showed that the assessment of quality of work life was average to high across all dimensions, with variations between them. The highest average was for the work environment dimension, followed by the job security dimension, while the lowest average was for participation in decision-making. The results also revealed statistically significant differences based on gender (in favor of females in some dimensions), educational qualifications (in favor of those with doctorates and master's degrees in specific dimensions), and years of experience. The results also demonstrated the importance of developing administrative systems and regulations, activating administrative participation, and supporting work-life balance as steps to improve the administrative work environment. The study concluded with a set of practical recommendations, most notably: greater involvement of the administrative body in the decision-making process, implementing fair and transparent administrative practices, providing a supportive work environment that respects the balance between the individual's professional and private life, intensifying professional development programs, and establishing an independent department concerned with the quality of work life within the Ministry of Education, which would be responsible for developing policies and strategies to improve the quality of administrative work. The researcher also recommended conducting similar studies covering other educational regions and incorporating psychological and social aspects into future evaluation frameworks.
Keywords: Quality of Work Life; Administrative Body; Work Environment; Job Satisfaction; Public Education; Riyadh Region